Óbitos associados ao HIV/AIDS de pessoas acompanhadas em serviço especializado: uma análise de sobrevivência - Chaves, Rebeca Bezerra (2018)
The AIDS epidemic is an important public health issue which is the principal cause of premature death in the world. Knowing the causes of death, risk factors, and clinical evaluation is the key factor for prevention and epidemic control, allowing the setting of priorities for the planning of public policies and healthcare management. The study aims to investigate deaths associated with HIV/AIDS in Joao Pessoa city – PB. It is an epidemiological, retrospective longitudinal study with qualitative approach done at two specialized care services in the urban center. The study population was 173 patients notified in YES in the period from 2007 to 2015. The inclusion criteria were patient with age 18 years old or above it who has been assisted in the specialized care and has the death certificate in his/her records. The exclusion criteria were incomplete records. The study used descriptive analysis and survival estimation of patients using survival analysis techniques, the KaplanMeier estimator, Log-normal parametric model, and Cox model. In the cases examined, the prevalence was male gender (67.1%), the age group between 30 and 49 years (60.7%), and heterosexuals (57.2%) who had a history of alcoholism (43.9% (80.3%) and used antiretroviral therapy (74%). They had sepsis as the principal cause of death (25.4%). Considering the log-rank test, there were important differences in terms of time of death for variables: sexual behavior, death cause, viral load, number of appointments by infectologists, T-CD4 lymphocyte counts, the use of TARV, TARV classification, the occurrence of hospitalizations, and abandonment of treatment and abandonment of clinical follow-up. The log-normal model had as significant covariates which influence on life expectancy, the following variables: age, schooling, the motive to search for a diagnosis, viral load, the use of TARV, and the number of hospitalizations. Regarding the Cox model, the variables were age, schooling, alcohol use, viral load, the use of TARV, and the number of hospitalizations were significant to explain the risk of the patient’s death. The models have shown relevant factors that influence in death occurrence when identifying a higher vulnerability among people who do not use TARV, are less than 40 years old, low schooling, viral load above 5,000 copies, with a diagnosis search through the signs and symptoms, and those who had only one hospitalization during their clinical follow-up. Therefore, the need to decrease the risk of death from the active search for early diagnoses as well from the first appointments using strategies that involve dialogues, orientations, and clarifications regarding the main questions that individuals diagnosed with HIV / AIDS can have.